Shared Services and Cost Reduction Motive in the Public Sector. Issue 9 (29th July 2017) - Tammel, Kaide
ABSTRACT: The intention of this article is to understand whether and how shared service centers can help reduce costs in the public sector context. We identify the sources of cost reduction for shared service centers and discuss the obstacles to making use of them. In order to illustrate and complement the theoretical discussion and the literature review, empirical insights from two Estonian cases are provided. The case studies indicate that when the context is enabling, shared service centers can help reduce back-office headcount. However, the total costs and benefits of the public-sector shared service centers are not calculated and remain unknown.